Clonal Propagation and Antibacterial Activity of Moringa Peregrina (Forssk) Fiori Plant - Hasan Alrayes, Linda Naim; Al Khateeb, Wesam “Moh’d Hadi; Mohamad Shatnaw, Mohamad Awad (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Moringa peregrina (Forssk) Fiori is one of the known medicinal plants in Jordan. It is used in traditional medicine to treat rheumatism and infections. Plant parts are used in the indigenous systems of human medicine for the treatment of a variety of ailments. Therefore, this study was conducted to investigate factors affecting M. peregrina in vitro propagation and its antimicrobial activity. Microshoots with apical meristem (10 or 15 mm in length) were subculture on MS medium supplemented with different concentration of BAP, Kinetin, Zeatin and Thidiazuron (TDZ). Maximum number of new shoots/explant (4.39) was obtained on Murashige and Skoog agar medium supplemented with 1.6 mg/L Zeatin. While at 0.4 mg/L BAP maximum shoot length was obtained (37.78 mm). Antibacterial activity of aqueous, methanolic, ethanolic, and acetonic extracts of both in vitro plantlets and ex vitro (field grown) M. peregrina were evaluated by the agar welldiffusion method against Klebsiella oxytoca ATCC 18182, Salmonella typhimurium ATCC 19430, Methicillin resistant, Staphylococcus aureus ATCC 29974, Klebsiella pneumonia ATCC13883, Proteus vulgaris ATCC 13315, Proteus mirabilis ATCC 12453, Enterobacter aerogenes ATCC 35029, Pseudomonas aeruginosa ATCC 27253, Escherichia coli O157:H7, Staphylococcus aureus ATCC 25923, Salmonella paratyphi ATCC 13076 and Escherichia coli ATCC 29522. The obtained results showed that ethanolic, acetonic and aqueous extracts revealed a wide antibacterial activity. Ethanolic extract of in vitro M. peregrina plantlets showed the maximum inhibition zone against Staphylococcus aureus.